The Utilization of Zakat Funds to Improve the Welfare of Mustahik: An Analysis of the BAZNAS South Sumatra Zmart Program - Rika Rahim; Rinol Sumantri; Abdullah Sahroni (El-Barka Journal of Islamic Economics and Business, 2025)
This study aims to analyze the utilization of zakat funds in improving the welfare of mustahik through the Zmart program managed by the National Zakat Agency (BAZNAS) of South Sumatra Province. The research uses a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation from both primary and secondary sources. The findings indicate that the Zmart program has a positive impact on improving the welfare of mustahik, particularly in increasing income, enhancing business skills, and fostering economic independence. The utilization of zakat funds through the Zmart program is proven to contribute to poverty reduction and economic empowerment. These results imply that productive zakat distribution can be an effective instrument for sustainable community welfare development.